Contribution to the knowledge of the Stipa-tenacissima Iberian grasslands (All. Stipion tenacissimae) - de la Torre, Antonio; Crespo, Manuel B.; Solanas, José Luis (Lazaroa, 2014)
A syntaxonomic revision of the Iberian "espartales" -dry grasslands dominated by Stipa tenacissima L.- is reoprted. Nomenclatural types as well as floristic, ecologic, dynamic and biographic data  (Stipion tenacissimae, Lygeo-Stipetalia, Lygeo Stipetea) is described for the thermophilous Alcoian espartales, and the name Heteropogono conforti-Stipeton tenacissimae is also validated for the thermophilous Valencian-Tarraconensian ones.